Intensive Quantification of Precipitation Moisture Sources in the Eastern Asian Monsoon Zone: A Modified Deuterium-excess-based Model - Fen Zhang; Tianming Huang; Zhonghe Pang (2022)
Defining moisture sources and evolution of precipitation is significant for further exploration of complex hydro-climatic interactions, especially under global warming with alternations of evapotranspiration capacity and precipitation moisture source structure. As a sensitive indicator, dexcess has been widely used to quantify the proportion of recycled vapor to precipitation (fre). However, existing models ignore taking transpiration vapor into account and the calculated fre tends to be lower than the true value. Herein, it was modified with transpiration vapor considered and applied in Guyuan, China located in a monsoon marginal zone with complex precipitation moisture sources. After modification, the estimated annual average fre was increased from 7.5% to 14.8%. This study highlights the contribution of transpiration vapor to precipitation and provides more information on the formation and evolution of precipitation to better serve future hydro-climatic research. The article has been published in the Geophysical Research Letters (https://agupubs.onlinelibrary.wiley.com/doi/10.1029/2021GL095909). <img src="data:image/jpeg;base64, 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